What can you see? - McGough, Kate (Pearson Education Hong kong, 2010)
"What Can You See?" is an engaging children's book that encourages young readers to explore their surroundings and observe the world around them. Through colorful illustrations and simple text, it invites children to identify various objects, animals, and elements in their environment, fostering observation skills and curiosity.